Systemic infection of Mycobacterium avium subspecies hominissuis and fungus in a pet dog - KANG, WoonKi; KIM, Yongbaek; KIM, JaeMyung; KIM, Myung-Chul; JANG, Yunho (Journal of Veterinary Medical Science, 2016)
A 3-year-old neutered female poodle with a long history of dermatophytic skin disease was presented with lethargy, anorexia and progressive weight loss. Abdominal ultrasonography revealed markedly enlarged mesenteric lymph nodes and multiple hypoechoic foci in the spleen. Cytology of the mesenteric lymph nodes and spleen showed granulomatous inflammation with fungal organisms and negatively stained intracytoplasmic bacterial rods consistent with Mycobacteria spp. Based on culture, multiplex polymerase chain reaction and sequence analysis, the bacterium was identified as Mycobacterium avium subspecies hominissuis. Despite treatment with antibiotics, the dog’s condition deteriorated, and it died approximately 3 weeks after first presentation.